Pengaruh Individual Characteristics, Job Characteristics Dan Organizational Characteristics Terhadap Employee Job Satisfaction PT. Thamrin Brothers Yamaha Center Kota Bengkulu - Suganda Firas Pratama; Tezar Arianto (UNIVED Press, 2023)
An organization often ignores other supporting factors for Employee Job Satisfaction, such as Individual Characteristics, Job Characteristics and Organizational Characteristics which must be considered in order to increase Employee Job Satisfaction. The purpose of this research is to determine the effect of individual characteristics, job characteristics, and organizational characteristics on the performance of employees of PT. Thamrin Brothers Yamaha Center Bengkulu City,This research was conducted at PT. Thamrin Brothers Yamaha Center Bengkulu City. The type of research used in this research is descriptive quantitative. The sample in this study were 50 permanent employees of PT. Thamrin Brothers Yamaha Center Bengkulu City. The sampling technique in this study was total sampling. Data collection techniques were observation, questionnaires and documentation. The data analysis technique used in this study was descriptive quantitative.The results show that Individual Characteristics individually affect Employee Job Satisfaction. Job Characteristics individually affect Employee Job Satisfaction. Organizational Characteristics individually affect Employee Job Satisfaction. Individual Characteristics, Job Characteristics and Organizational Characteristics simultaneously affect Employee Job